An Open-Source Scalable Thermal and Power Controller for HPC Processors - Bambini, Giovanni; Balas, Robert; Conficoni, Christian; Tilli, Andrea; Benini, Luca; Benatti, Simone; Bartolini, Andrea (Proceedings - IEEE International Conference on Computer Design, 2020)
In the last decade, high performance multi-core processor designs have followed an increase in number of cores, interfaces, heterogeneity and System-on-chip (SoC) complexity. HPC applications also require tailored chip designs with specific operating points and performance indexes. In this scenario, an advanced and configurable Power Controller System (PCS) is necessary to meet power and thermal constraints, without the necessity of static ultra-conservative margins on the operating points. In this paper, we propose an open-source PCS design, based on a parallel ultra-low power microcontroller with RISC-V cores, and an open-source software environment based on a Real-time operating system (RTOS) with a configurable Power-thermal control algorithm. Considering a 1ms control interval, the overhead of the RTOS is about 6% of the cycles in the nominal case. The control algorithm is able to limit temperature and power consumption within given bounds, while maximizing performance. The PCS is able to control up to 76 different cores/computing units with headroom for larger core counts.